"Some sort of fantasy land": A qualitative investigation of appropriate prescribing in cancer care. Issue 3 (12th September 2019) - Ghinea, Narcyz; Wiersma, Miriam; Kerridge, Ian; Olver, Ian; Pearson, Sallie; Day, Richard; Liauw, Winston; Lipworth, Wendy
Abstract: Rationale, aims, and objectives: Increasing the appropriateness of prescribing has long been a focus of government, non‐government, and professional organizations. Progress towards this is made difficult by the fact appropriate prescribing remains inconsistently defined and is the subject of ongoing intense disagreement. In this study, we attempted to understand why this is the case within the context of oncology and haematology. Methods: We performed a qualitative empirical analysis of semi‐structured interviews with 16 Australian oncologists and haematologists. Results: We found that oncologists framed appropriate prescribing in terms of the following inter‐related, and at times opposed, values: civic mindedness, hope and compassion, realism, and virtue in motivation. Conclusions: These values cannot be ranked a priori, and therefore, any definition of appropriate prescribing must be aligned with what communities want from their health system. When one value is privileged over another in any specific context, a compelling argument must be provided to justify the choice. In an era of shared decision making, patient rights, and high‐cost medicines, we need to reassess what we mean by appropriate prescribing in cancer care.